2023
DOI: 10.3390/foods12061179
|View full text |Cite
|
Sign up to set email alerts
|

Current Perspectives on Viable but Non-Culturable Foodborne Pathogenic Bacteria: A Review

Abstract: Foodborne diseases caused by foodborne pathogens pose risks to food safety. Effective detection and efficient inactivation of pathogenic bacteria has always been a research hotspot in the field of food safety. Complicating these goals, bacteria can be induced to adopt a viable but non-culturable (VBNC) state under adverse external environmental stresses. When in the VBNC state, pathogens cannot form visible colonies during traditional culture but remain metabolically active and toxic. The resulting false negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 83 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…However, RNA is generally less stable than DNA and can degrade quickly when exposed to environmental factors, such as temperature, pH, and enzymatic activity [70]. Another approach involves the application of viability dyes, such as propidium monoazide (PMA), DyeTox13, or thiazole orange monoazide (TOMO) [14,71]. Previous studies have indicated that these dyes could inhibit signals arising from dead cells [72,73].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, RNA is generally less stable than DNA and can degrade quickly when exposed to environmental factors, such as temperature, pH, and enzymatic activity [70]. Another approach involves the application of viability dyes, such as propidium monoazide (PMA), DyeTox13, or thiazole orange monoazide (TOMO) [14,71]. Previous studies have indicated that these dyes could inhibit signals arising from dead cells [72,73].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that these dyes could inhibit signals arising from dead cells [72,73]. However, the effectiveness of these dyes may be influenced by the food matrices and bacterial species [71]. Thus, future studies are suggested to explore the effectiveness of these dyes in combination with the PCR-CE assay for detecting live foodborne pathogens in various food samples.…”
Section: Discussionmentioning
confidence: 99%
“…Note that most studies involving PMA treatment were PCR-based methods ( Tables S1-2 ), and scant information exists concerning its integration with isothermal amplification techniques. Previous studies have pointed out that employing PMA to differentiate between DNA originating from live and death cells encounters several challenges, including the influence of food matrices, heat treatment, and the concentration of bacterial cells ( Lv et al, 2020 , Petersen et al, 2021 , Zhang et al, 2023 ). Therefore, the design and optimization of the treatment conditions for using PMA coupled with a certain amplification method are necessary.…”
Section: Remaining Challenges and Possible Opportunitiesmentioning
confidence: 99%
“…In the food industry, microorganisms can adhere to packaging surfaces, form a biofilm, and compromise the shelf-life of food products (Galié et al, 2018;Carrascosa et al, 2021). In addition, studies show that bacteria in a biofilm state are more likely disposed to enter in the "viable but nonculturable" (VBNC) condition, where the cells are unable to grow and replicate on standard solid culture media, eluding detection by using conventional microbial culture-based techniques (Li and Zhao, 2020;Qi et al, 2022;Zhang et al, 2023). In this scenario, flow cytometry (FCM) emerges as a real-time technique for identifying the culture-uninvestigable cellular physiological state.…”
Section: Introductionmentioning
confidence: 99%